2012
DOI: 10.1016/j.ydbio.2012.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Epsin's role in Notch ligand cells requires three Epsin protein functions: The lipid binding function of the ENTH domain, a single Ubiquitin interaction motif, and a subset of the C-terminal protein binding modules

Abstract: Epsin is an endocytic protein that binds Clathrin, the plasma membrane, Ubiquitin, and also a variety of other endocytic proteins through well-characterized motifs. Although Epsin is a general endocytic factor, genetic analysis in Drosophila and mice revealed that Epsin is essential specifically for internalization of ubiquitinated transmembrane ligands of the Notch receptor, a process required for Notch activation. Epsin’s mechanism of function is complex and context-dependent. Consequently, how Epsin promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 81 publications
(143 reference statements)
1
34
0
Order By: Relevance
“…Nonetheless, mouse embryos lacking both epsin1 and epsin2 display classic Notch mutant phenotypes, likely reflecting a role for epsins in ligand signaling activity and underscoring the absolute requirement for epsins in Notch-dependent events. Furthermore, since Dll1 ubiquitylation and epsin UIMs are required for Dll1-epsin complex formation, Dll1 cell-mediated force and Delta signaling activity in flies (Xie et al, 2012), we hypothesize recruitment of epsins by ubiquitylated ligands is critical for endocytic force to activate Notch.…”
Section: Discussionmentioning
confidence: 98%
“…Nonetheless, mouse embryos lacking both epsin1 and epsin2 display classic Notch mutant phenotypes, likely reflecting a role for epsins in ligand signaling activity and underscoring the absolute requirement for epsins in Notch-dependent events. Furthermore, since Dll1 ubiquitylation and epsin UIMs are required for Dll1-epsin complex formation, Dll1 cell-mediated force and Delta signaling activity in flies (Xie et al, 2012), we hypothesize recruitment of epsins by ubiquitylated ligands is critical for endocytic force to activate Notch.…”
Section: Discussionmentioning
confidence: 98%
“…Epsin also has motifs for interaction with AP2 and clathrin. In a recent study, one of the two UIMs, and the ENTH domain have been shown to be essential for Notch signaling [54]. In the same study, the clathrin binding motifs on the C-terminal region were dispensable although the extended region encompassing these and motifs for interaction with AP2 were necessary for Epsin function in Notch signaling.…”
Section: Endocytic Trafficking Of Dsl Ligandsmentioning
confidence: 95%
“…The factor accounting for ubiquitinated ligand recognition is Epsin (Lqf in Drosophila ), a clathrin-interacting endocytic adaptor that is thought to bind the ligands through its ubiquitin interacting motif (UIM) [108,112114]. Epsin’s role in ligand-emitting cell is rather complex and requires three epsin functional domains [114]: the ENTH (Epsin- N -Terminal Homology) domain binds PIP2 (phosphatidylinositol 4,5-biphosphate), inserts into the plasma membrane and induces membrane curvature. Then the epsin C -terminus recruits clathrin directly and also AP-2 and/or Eps15 to eventually promote clathrin-dependent ligand endocytosis.…”
Section: How Ubiquitinations Regulate Notch Pathwaymentioning
confidence: 99%